Visual execution of caesar cipher methods and its application - Nur Syafiqa, Ismail (2014)
Visual Execution Of Caesar Cipher Methods And Its Application is developed for beginner to learn basic encryption process and inspect what is actually happen during encryption and decryption process in visualization approach. Most of cryptography tools developed and provide in the net is only able to encrypt and decrypt the data without explaining how do the process take place. The methodology used to implement this project is based on the Object Oriented Cycle Model. This project can contribute on logical understanding and to ensure beginner able to applied the theory in a real environment. The important things considered in this program is explanation as an introduction about the Cipher chosen before continue to next lesson. This program is divided into three sequential phase for each cipher. The first phase is briefly explanation about the cipher and how it work. The explanation is deliver in form of wording explanation. Second phase is demo on how the cipher is encrypted and decrypted. The last phase need totally user interaction with the application where the user need to enter the plaintext, enter the key, execute and exit. The process is presented by using visualization execution. This program also considered more about the interface. Simple interface which holds two panels dedicated to write or paste the text for encryption or decryption, and the other panel for viewing execution concept is implement. Besides that, button for play, pause, stop, next, previous and end also provided to ensure user can use the application easily. This can help user easily do understand the concept well. Other than that, this program also provide brute force attack panel to view brute force list for each keys. The cipher covered for this program is Caesar Cipher methods.